Elastic and inelastic scattering of 18O ions on 12C nuclei - A. T. Rudchik; Yu. O. Shyrma; E. I. Koshchy; S. Kliczewski; B. G. Novatsky; O. A. Ponkratenko; E. Piasecki; G. P. Romanyshyna; K. Rusek; Yu. M. Stepanenko; I. Strojek; S. B. Sakuta; et al. (Âderna Fìzika ta Energetika, 2009)
Angular distributions of the 12C + 18O elastic and inelastic scattering were measured at the energy Elab(18O) = 105 MeV (Ec.m. = 42 MeV). These data and data known from the literature at the energies Ec.m. = 12.9 - 56 МеV were analysed within the optical model and coupled-reactionchannels method. The sets of the Woods-Saxon (12С + 18O)-potential parameters were deduced and their energy dependence was studied. It was found the isotopic differences in the (12С + 16O)- and (12С + 18O)-potentials parameters and in their surface forms. The mechanisms of elastic and inelastic (12С + 18O)-scattering and role of transfer reactions were studied.